Gastric cancer peritoneal metastasis: a bibliometric study from 2000 to 2024 using VOSviewer software - Y, Manting; L, Dongfang (Frontiers in Oncology, 2025)
BackgroundGastric cancer remains a prevalent malignancy worldwide, with peritoneal metastasis being the predominant form of recurrence and metastasis, which are clear predictors of prognosis. The aim of this comprehensive bibliometric analysis was to assess the current status of the research landscape and to identify impending trends in gastric cancer peritoneal metastasis (GCPM).MethodsRelevant studies of GCPM were retrieved from the Web of Science Core Collection database. Qualified articles were screened based on the inclusion and exclusion criteria for further analysis. The selected publications were then subjected to bibliometric analysis utilizing VOSviewer software.ResultsIn total, 1,100 publications were included for analysis. The results revealed a consistent upward trend in the number of publications annually from 2000 to 2024, with an anticipated continuation of this growth in future research. The National Cancer Center Japan, emerged as the institution with the most publications and Professor Kodera and Annals of Surgical Oncology were identified as the most influential author and journal, respectively, in the domain of GCPM. In terms of international collaborations, the USA, Japan, and France were the most engaged countries. Yonemura was recognized as the most frequently cited author. Gastrectomy, systemic chemotherapy, and intraperitoneal therapy are the current research hotspots within this domain.ConclusionResearch related to GCPM had rapidly increased over the past two decades. These findings identify the most influential countries, institutions, authors, journals, and academic collaboration networks, while also clarifying hotspots and future trends in GCPM research.